Evaluation of the performance of community-based natural resources management (CBNRM) projects along an aridity gradient in Botswana - Mpofu, Khulekani (Rhodes University, Faculty of Science, Department of Environmental Science, 2013)
The Botswana Community Based Natural Resources Management (CBNRM) programme started in 1989. Its aims were to promote sustainable development through sustainable natural resources management and utilisation to improve rural livelihoods. The country CBNRM programme has recorded mixed outcomes and this has raised questions on the programme performance throughout the country. Since the programme has been recognised as one of the eight main livelihood strategies for rural communities in Botswana, there was a need to evaluate the programme performance and determine the factors that influence it. This thesis therefore evaluated the performance of CBNRM projects along an aridity gradient in Botswana and by so doing answered the two research questions of: (1) What factors influence the performance of CBNRM? And (2) how does aridity influence the performance of CBNRM programmes? Performance was determined in terms of financial benefits generated by CBNRM projects and the projects adherence to the CBNRM principles. Data were collected from seven selected CBNRM projects covering three aridity zones (wet, medium rainfall and dry areas) in the country. Data were also collected from key informants and community based organisations (CBO) project managers. Research findings have indicated differences in the performance of CBNRM projects across the identified three aridity zones. Factors that influenced the performance of CBNRM projects varied among the three aridity zones. These factors included: existence of complimentary rules and regulations for managing CBNRM projects; literacy levels of communities involved in CBNRM; ethnic composition of the project communities; historic and current socio-economic trends within communities; collaboration between CBNRM institutions and other local level institutes; amount of benefits generated through the projects; ability of institutions to resolve outstanding issues in time and type of CBNRM project. Research results also indicated that there was variation in the performance of CBNRM projects across the three aridity zones. Aridity was found to directly influence the performance of CBNRM projects through its influence on the amount of revenues that projects generated.
Keywords: Community-Based Natural Resource Management in Southern Africa (Project); Natural resources, Communal -- Botswana; Natural resources -- Management -- Botswana; Natural resources -- Management -- Economic aspects -- Botswana; Conservation of natural resources -- Botswana; Conservation of natural resources -- Economic aspects -- Botswana; Arid regions -- Botswana; Natural resources -- Management -- Citizen participation -- Botswana